2015
DOI: 10.1260/1747-9541.10.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Induced by Repeated Maximal Efforts is Specific to the Rugby Task Performed

Abstract: The aim of this study was to analyze fatigue occurrence during the repetition of rugby union specific tasks. Eight high-level rugby players (age 23 ± 1.1 y; body mass 90.9 ± 9.8 kg; height 1.83 ± 7.3m) performed three sessions, in a random order, to investigate specific rugby union tasks (Scrum, Maul and Running sprints). Each session consisted in 5 repetitions of 5-s maximal exertion interspersed with 20-s passive recoveries. The scrums were performed into a fixed yoke, while the mauls were realized into a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(83 citation statements)
references
References 28 publications
3
76
3
1
Order By: Relevance
“…To our knowledge no previous study focused on the influence of fatigue on the engagement phase. However, considering the average force, the present results are not in accordance with those of Morel et al (2015) which showed a decrease after five scrums. This discrepancy could be attributed to the different scrum conditions used.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…To our knowledge no previous study focused on the influence of fatigue on the engagement phase. However, considering the average force, the present results are not in accordance with those of Morel et al (2015) which showed a decrease after five scrums. This discrepancy could be attributed to the different scrum conditions used.…”
Section: Discussioncontrasting
confidence: 99%
“…These two parameters indicate a strong neural drive reduction (i.e., central fatigue) which confirmed the scrummaging‐induce‐central‐fatigue hypothesis previously made by Morel et al. (). Furthermore, the 12.6 ± 5.5% erector spinae electromyographic signal decrease suggested that the central motor drive may be impaired in other critical muscle groups when scrummaging.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A reduction in muscle contractility and a decline in voluntary activation of the vastus lateralis has been purported and that both peripheral and central mechanisms may be responsible for scrummaging fatigue [14]. However, previous studies have only examined one or two muscles [13,14] and the activation levels of other muscles during scrummaging in front row forwards warrant further investigation [4,13,14,20]. Furthermore, the assessment of lower limb and 'core' muscles, (gluteus maximus, gastrocnemius, and the abdominal complex) have been inadequately examined and little is known…”
Section: Introductionmentioning
confidence: 99%